Propose Model of Gathering System Optimization on Unit-G4 Geothermal Power Plant - Udi Harmoko; Sorja Koesuma; Joko Windarto; Asep Yusup Burhanudin (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2025)
The nature of geothermal heat is a decrease in pressure, temperature, and steam flow. Based on Exaquantum observation data, one of the geothermal power plants in West Java experienced a reduced steam supply for the Geothermal Power plant (GPP) Unit-G4, which decreased production capacity. This study aims to analyze the existing conditions and make models and simulations on the optimum Steam Gathering System (SGS) at GPP Unit-G4.  The stages in this research are modelling using Aspen Hysys software on the existing conditions of SGS as a basis for finding alternative optimum solutions. The second stage was to design a model and simulation by interconnecting the K-21X production well with the PL-X05 production.  Furthermore, the simulation of adding steam by 25%, 50%, 75%, and 100% in the interconnection process was carried out. Existing steam gathering modelling and simulation results show that the deviation between actual steam field parameters is ≤ 2% (can be used as a simulation baseline). The modelling and simulation results of adding steam from the K-21X production well to the PL-X05 production well are optimum at 100% and 75% steam addition. From the simulation, adding 25% and 50% steam cannot be applied because the net power does not reach the unit rate capacity of 60.856 MW.